Sifat Organoleptik Madumongso Tape Ubi Ungu dengan Perbedaan Proporsi Tape Ketan Hitam dan Tape Ketan Putih - Ardansyah Putra Hariyanto; Lilis Sulandari; Ita Fatkhur Romadhoni; Andika Kuncoro Widagdo (Jurnal Bintang Pendidikan Indonesia, 2024)
Madumongso in this research is a processed product made from purple sweet potato tape, black sticky rice tape, and white sticky rice tape which is processed by mixing supporting ingredients such as sugar, coconut milk and pandan using low heat. Round shape wrapped in plastic and crepe paper. Optimal organoleptic characteristics can increase consumer acceptance and the combination of these ingredients can increase the nutritional content of the product. The aim of this product is 1) to determine the organoleptic properties which include shape, color, taste, texture, 2) to determine the nutritional content of madumongso purple sweet potato tape with the difference in proportions of black sticky rice tape and white sticky rice tape. This type of research is experimental. The data collection technique used was observation through 5 training panelists and 25 semi-practice panelists who were assisted with assessment observation sheets 1-5. The independent variables in this research are purple sweet potato tape, black sticky rice tape and white sticky rice tape, the dependent variables in this research are shape, color, taste and texture, and the control variables in this research are the type of equipment, raw materials and manufacturing techniques. Data analysis in this study used one-way ANOVA. The results of this research show 1) there is no influence on color and texture, 2) there is an influence on shape, taste and level of liking for the purple sweet potato madumongso tape product.